Egg Consumption and Incidence of Heart Failure: A Meta-Analysis of Prospective Cohort Studies - Khawaja, Owais; Singh, Hemindermeet; Luni, Faraz; Kabour, Ameer; Ali, Syed S.; Taleb, Mohammed; Ahmed, Hafeezuddin; Gaziano, John Michael; Djoussé, Luc (Frontiers in Nutrition, 2017)
Introduction: Heart failure (HF) remains a major health problem affecting 5.7 million adults in USA. Data on the association of egg consumption with incident HF have been inconsistent. We therefore conducted this meta-analysis of prospective cohort studies to assess the relation of egg consumption with incident HF in the general population. Methods: Using extensive online search, we conducted a meta-analysis of new onset heart failure following exposure to egg consumption. A random-effect model was used and between studies heterogeneity was estimated with I2. Publication bias was assessed graphically using a funnel plot. All analyses were performed with Comprehensive Meta-Analysis (version 2.2.064). Results: We identified 4 prospective cohorts for a total of 105,999 subjects and 5,059 cases of new onset HF. When comparing the highest (>1/day) to the lowest category of egg consumption, pooled relative risk (RR) of HF was 1.25 (95% CI = 1.12-1.39; p= 0.00). There was no evidence for heterogeneity (I2=0%) nor publication bias. On sensitivity analysis stratification by gender differences, follow up duration, and region where study was conducted did not alter the main conclusion. Conclusions: Our meta-analysis suggests an elevated risk of incident HF with frequent egg consumption.